1967
DOI: 10.2466/pr0.1967.20.3.975
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Components of Test Anxiety: A Distinction and Some Initial Data

Abstract: This study examined the relationship between two aspects of the TAQ, identified as “worry” and “emotionality,” and performance expectancies on a college examination. For this purpose, a short Pre-examination Questionnaire was developed. As predicted, worry (W) was inversely related to performance expectancy. No relationship between expectancy and emotionality (E) was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
524
4
53

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 940 publications
(592 citation statements)
references
References 4 publications
11
524
4
53
Order By: Relevance
“…The Intrinsic Value scale (a = .87) was constructed by taking the mean score of the student's response to nine items concerning intrinsic interest in ("I think what we are learning in this Science class is interesting") and perceived importance of course work ("It is important for me to learn what is being taught in this English class"; cf., Eccles, 1983) as well as preference for challenge and mastery goals ("I prefer class work that is challenging so I can learn new things"; cf., Harter, 1981). Four items (e.g., "I am so nervous during a test that I cannot remember facts I have learned," "When I take a test I think about how poorly I am doing"; cf., Liebert & Morris, 1967) concerning worry about and cognitive interference on tests were used in the Test Anxiety scale (a -.75).…”
Section: Methodsmentioning
confidence: 99%
“…The Intrinsic Value scale (a = .87) was constructed by taking the mean score of the student's response to nine items concerning intrinsic interest in ("I think what we are learning in this Science class is interesting") and perceived importance of course work ("It is important for me to learn what is being taught in this English class"; cf., Eccles, 1983) as well as preference for challenge and mastery goals ("I prefer class work that is challenging so I can learn new things"; cf., Harter, 1981). Four items (e.g., "I am so nervous during a test that I cannot remember facts I have learned," "When I take a test I think about how poorly I am doing"; cf., Liebert & Morris, 1967) concerning worry about and cognitive interference on tests were used in the Test Anxiety scale (a -.75).…”
Section: Methodsmentioning
confidence: 99%
“…Test anxiety defines two indices of "concern", and "excitement". "concern" meant having cognitive anxiety on the aftermaths of failing (Liebert & Morris, 1967); and "excitement" causes psychological changes which are the results of automatic innervation (Spielberger & Vagg, 1995). Therefore, it seems that negative and ineffective thoughts interfere with cognitive process on exam session, and result in diminishing students' performance (Crişan & Copaci, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by results presented in research on test and clinical anxiety (Davidson & Schwartz, 1976;Liebert & Morris, 1967), which proposed a division of the anxiety construct into a cognitive (worry) and somatic (emotionality) component, Martens et al (1990a) suggested the Multidimensional Anxiety Theory to predict sport performance. Specifically, cognitive anxiety was hypothesised to be negatively and linearly related to performance and to vary throughout the competition.…”
Section: Multidimensional Anxiety Theory Of Performance Assessed By Tmentioning
confidence: 99%
“…Based on test-anxiety research in educational psychology, the cognitive element of anxiety was labelled as "worry" and was defined as individuals' cognitive concerns and negative self-expectations, worry about the situation and possible consequences. The somatic component was instead referred to as "emotionality" and defined as the individuals' perceptions of physiological and affective elements of anxiety, including indications of autonomic arousal and unpleasant symptoms such as tension and nervousness (Liebert & Morris, 1967;Morris, Davis, & Hutchings, 1981). In the clinical literature, a distinction was instead made between "cognitive anxiety" (i.e., conscious awareness of unpleasant feelings about oneself or external stimuli, worry and disturbing visual images), "somatic anxiety" (awareness of, for instance, blushing, increased heart rate and muscular symptoms), and "attentional disturbances" (Davidson & Schwartz, 1976).…”
Section: Competitive State Anxietymentioning
confidence: 99%
See 1 more Smart Citation